2009
DOI: 10.1080/15305050903106891
|View full text |Cite
|
Sign up to set email alerts
|

The WISC-III Profile in Greek Children with Learning Disabilities: Different Language, Similar Difficulties

Abstract: This study investigates the WISC-III profile in Greek children with learning disabilities (LD). The sample consisted of 180 children diagnosed with learning disability (136 boys, 44 girls) aged 6.11 to 14.4 years. The Mean Full-scale IQ is 96.08, Mean Verbal IQ is 96.38, and Mean Performance IQ is 96.61. On individual subtests, the lowest mean scores are for Digit Span and Arithmetic whereas the highest are for Similarities and Picture Completion. Forty eight percent of our sample has a higher Verbal Intellige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
(50 reference statements)
1
8
0
5
Order By: Relevance
“…Table shows the percentage of the discrepancies between VIQ and PIQ, compared with the findings of Daley and Nagle () and Rotsika et al . (). Thirty‐eight percent of normal readers and 44.9% of children with DD had a difference ≥11 points.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table shows the percentage of the discrepancies between VIQ and PIQ, compared with the findings of Daley and Nagle () and Rotsika et al . (). Thirty‐eight percent of normal readers and 44.9% of children with DD had a difference ≥11 points.…”
Section: Resultsmentioning
confidence: 99%
“…Nonsignificant differences were found in the Verbal–Performance discrepancy, and the mean difference was smaller than for normal readers. This finding was also reported by other studies with LD (Pereira & Simões, ) and children with DD (Rotsika et al ., ) and demonstrated the minimal practical value of the VIQ‐PIQ discrepancy for differential diagnosis (Kaufman, ). The analyses of IQ mean scores between groups revealed that dyslexics had significantly lower scores in FSIQ and VIQ, which is consistent with a large number of studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations